Treatment of Molluscum Contagiosum by Potassium Hydroxide Solution 20% with and Without Pricking and By Pricking Alone: A Comparative Study with Review of Literature - Azar Hadi Maluki; Qutaiba Jawad Kadhum (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
Background: Molluscum Contagiosum is a common viral skin infection, caused by poxvirus, commonly affects young children. Although there is no specific treatment for this infection, many therapeutic modalities has been used with different success rates. Objectives: To evaluate the effectiveness of topical 20% KOH, 20% KOH with pricking and pricking alone as comparative treatments for molluscum contagiosum. Patients and methods: This study was conducted in the Dermatology Clinic of Kufa Medical School Teaching Hospital in Iraq, from August 2011 to January 2013. Ninety patients with Molluscum Contagiosum were recruited. Diagnosis of Molluscum Contagiosum was confirmed on clinical bases. Patients with prior treatment for the last month and patients who had inflamed lesions were excluded. Full history and physical examination were done for all Patients. The patients were divided into three groups: Group 1included 30 patients treated with topical KOH 20% applied by wooden stick daily at bed time. Group 2 included 30 patients treated by pricking the lesions by 27 G needle wet in 20% KOH weekly. Group 3 included 30 patients treated by pricking alone once weekly. Treatment sessions were continued until complete cure or maximum of four sessions was achieved. The patients were followed up for two months period from the last session. Results: Out of the ninety patients, 57 completed the study. There were thirty one (54.3%) males and 26 (45.6%) females with male to female ratio 1.19-. Their ages ranged from 1.5-62 years (mean and standard deviation of 19.4±16.7). The most common age group affected was below 12 years, 29 (50.8%) patients. The most commonly affected body sites were the face and neck, 49 (85.9%) patients. After 4 sessions, the response rate was as follows: - Group 1, 17 (94.4%): patients were cured completely and relapse was not recorded; p-value was highly significant (=0.0019). - Group 2, 20 (86.4%) patients were completely cured and relapse was not recorded; p-value was highly significant (< 0.001). - Group 3, 12 (75%) patients were completely cured and relapse was not recorded; p-value was highly significant (=0.0014). Conclusion: Pricking Molluscum Contagiosum by 27G needle alone, pricking with 20% KOH and topically applied 20% KOH all achieved comparable success rates that were all statistically significant. All three methods represented tolerable and highly effective modes of therapy.